A novel glass polyalkenoate cement for fixation purposes in the skeleton / Adel Moh'd Fawzi A. R. Alhalawani - Adel Moh'd Fawzi, A.R. Alhalawani (2014)
Healing complications following median sternotomy result from poor sternal fixation and contribute to mortality and morbidity. This study investigates the use of novel gallium (Ga) based glass polyalkenoate cements (GPCs) for improved sternal fixation post-sternotomy. The glass series consists of a Control (CaO-ZnO-SiO2), and LGa-1 and LGa-2 which contain gallium (Ga) at the expense of zinc (Zn) in 0.08 mol% increments. X-ray diffraction (XRD) and particle size analysis (PSA) showed that all glasses were fully amorphous with a similar mean particle diameter. The glass series was formulated with E11 Poly(acrylic acid) (PAA) at 50 wt% addition. The additions of Ga result in both an increased working time (75 s to 137 s) and setting time (113 to 254 s). Fourier transform infrared spectroscopy (FTIR) analysis indicated that this was a direct result of increased unreacted poly(acrylic acid) (PAA) and the reduction of crosslink formation during working and setting times. The increasing presence of Ga resulted in an altered ion release profile with increased Ca, Zn, Si and Ga ions released into solution, with the 30 day solution displaying the largest content of all ions. Addition of Ga was also found to decrease the contact angle, representing more hydrophilicity and adhesive properties. Surface morphology and roughness (Ra) measurements made using Atomic Force Microscopy (AFM) showed that the addition of Ga increases Ra. Mechanical properties were reproducible and resulted in improved biaxial flexural strengths (σf) with the addition of Ga, with LGa-2 peaking at 29 MPa after 30 days, however, the additions of Ga had relatively no effect on the flexural strength with cement maturation. Compressive strength (σc) was decreased by the Ga addition, however, LGa-2 presented comparable values (17, 30 and 33 MPa) to the Control glasses (19, 31 and 33 MPa) after 1, 7 and 30 days, respectively. Ex-vivo tensile strengths proved that the LGa samples (0.16 wt% Ga) are comparable to the Control samples. The strengths for Control cements were ~0.4, 0.6 and 0.5 MPa for 1, 7 and 30 days measurements, respectively. While LGa-2 strength values are ~0.3, 0.4, 0.4 MPa respectively, tested over the same periods. A scanning electron microscopy (SEM) survey revealed that all failures are adhesive, while energy dispersive x-ray analysis (EDX) presented high concentration values of all incorporated ions when compared with the ion release studies. Results show that LGa-2 can be used for sternal closure due to its novel characteristics in GPCs, including biocompatibility, improved handling properties, adhesion-ability, and chemotherapeutic properties, appropriate strength, and bone regeneration effects. Similar to any ex-vivo study, the main limitation of this project was the inability to consider the complications regularly encountered during sternotomy, such as bleeding and osteoporosis. Design limitations included testing of small bovine sterna, differing from the human sternum in dimension, and the inability to mimic the exact directions of physiological forces. Further, the use of formaldehyde is a potential complicating factor given its toxicity and unknown effect on the bioactive glass.